The risk of depression and anxiety is not increased in individuals with juvenile idiopathic arthritis - results from the south-Swedish juvenile idiopathic arthritis cohort - Elisabet Berthold; Alma Dahlberg; Anna Jöud; Helena Tydén; Bengt Månsson; Fredrik Kahn; Robin Kahn (BMC, 2022)
Abstract Background Children with chronic diseases are reported to have increased risk of psychiatric comorbidity. Few studies have investigated this risk in juvenile idiopathic arthritis (JIA), with conflicting results. We performed a population-based, longitudinal cohort study of the risk of depression and anxiety in south-Swedish patients with juvenile arthritis. Methods The south-Swedish JIA cohort (n = 640), a population-based cohort with validated JIA diagnosis 1980 - 2010 and comparators, a reference group of 3200 individuals free from JIA, matched for sex, year of birth and residential region, was used. Data on comorbid diagnosis with depression or anxiety were obtained from the Skåne Healthcare Register, containing all healthcare contacts in the region, from 1998 to 2019. We used Cox proportional models for the calculation of hazard ratios. Results During the study period, 1998 to 2019, 93 (14.5%) of the individuals in the JIA group were diagnosed with depression, and 111 (17.3%) with anxiety. Corresponding numbers among the references was 474 (14.8%) with depression and 557 (17.4%) with anxiety. Hazard ratio for depression was 1.1 (95% CI 0.9 - 1.5) in females and 0.8 (95% CI 0.5 - 1.4) in males, and for anxiety 1.2 (95% CI 0.9 - 1.5) in females and 0.6 (95% CI 0.4 - 1.1) in males. There were no statistically significant hazard ratios when analyzing subgroups of JIA patients with long disease duration or treatment with disease-modifying antirheumatic drugs. Conclusions Individuals with JIA do not have any statistically increased risk of being diagnosed with depression or anxiety compared to matched references.